Gấp với ạ anh chị m.n ơi !!!!!!!!!!!!!!!!!!!!!!! Đề: Rút gọn biểu thức sau 4x (x+3) – (2x-1)$^2$

Gấp với ạ anh chị m.n ơi !!!!!!!!!!!!!!!!!!!!!!!
Đề: Rút gọn biểu thức sau
4x (x+3) – (2x-1)$^2$

2 bình luận về “Gấp với ạ anh chị m.n ơi !!!!!!!!!!!!!!!!!!!!!!! Đề: Rút gọn biểu thức sau 4x (x+3) – (2x-1)$^2$”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
      4x( x + 3 ) – ( 2x -1 )^2
    = 4x.x + 4x.3 – ( 4x^2 – 4x + 1 )
    = 4x^2 + 12x – 4x^2 + 4x – 1
    = ( 4x^2 – 4x^2 ) + ( 12x+ 4x ) -1
    = 0 + 16x – 1
    = 16x – 1

    Trả lời

Viết một bình luận

Câu hỏi mới